Towards a geographical political economy understanding of platformization - Ecker, Yannick; Münßinger, Max (Progress in Economic Geography, 2024)
In the last ten years digital platforms have emerged as an important theme in academic discourse and various subdisciplines of geography and adjacent research areas. Whether in the fields of social media, urban transport, industry cloud services or gig work, platformization is therein often discussed as a more-than-economic phenomenon engaging in a conflictive relationship with public interest, sovereignty, regulation and the state. However, while the concept of the platform has become ubiquitous, the integration of and dialogue between various broadened definitions are less often practiced. In our short paper, we argue that for further addressing this intricate relation between platforms, power and sovereignty an engagement with the platform concept and its integration through a political economy understanding is key for two reasons: Firstly, an overarching concept of platformization transcending the political/economy binary is necessary to be able to problematize the reification of normalized economic practices lying at the heart of the phenomenon. Secondly, there is a pragmatic reason for developing a geographical political economy perspective on platformization as it can serve as a common ground for an engaged pluralism within and beyond the discipline of economic geography. Based on a systematization of existing definitions this paper therefore combines insights from political economy perspectives, urban platform research and research on platform labor to propose a working definition stimulating a reflection on the platform discourse thus far and strengthening strategical-relational thinking on platform power in future researc
Keywords: Digital geographies; Economic geography; Platformization; Political Economy; State